Building Global Connections Without Losing National Identity: The Use of English as a Lingua Franca in Global Communication - Anggelica Scholastika; Novarysta Agustina Da Cruz; Srimulyani Beleng; Candra Ekwan Dubu; Alfret Benu; Elisna Huan (Peneliti.net, 2026)
Globalization and the digital revolution have propelled English to function as English as a Lingua Franca (ELF), namely a global means of communication that bridges speakers from different linguistic backgrounds. For Indonesia, this phenomenon presents a dilemma: proficiency in English is required to enhance global competitiveness; however, on the other hand, it raises concerns regarding the preservation of national identity, Pancasila values, and the Indonesian language. Previous studies have predominantly focused on linguistic and pedagogical aspects, while the citizenship perspective remains underexplored. This article aims to analyze the relationship between the use of ELF and efforts to maintain Indonesia’s national identity by employing a literature review method based on a descriptive-analytical approach. The sources reviewed include journal articles, books, and academic publications related to ELF, global communication, and national identity. The findings indicate that ELF can generate both positive and negative impacts on national identity; nevertheless, English should not necessarily be perceived as a cultural threat. Two main strategies are proposed: (1) implementing the concept of glocalization, namely positioning English as an instrumental communication tool rather than a lifestyle, while the Indonesian language continues to be upheld as the home of the nation’s cultural and emotional values; and (2) adopting the intelligibility paradigm in English language learning, enabling younger generations to communicate confidently without eliminating local characteristics, including Indonesian accents and distinctive norms of politeness. Therefore, when balanced with a strong foundation of national character, ELF can serve as a strategic instrument for expanding influence while simultaneously promoting the richness of Indonesia’s national identity on the global stage